2011
DOI: 10.1111/j.1365-2923.2011.03934.x
|View full text |Cite
|
Sign up to set email alerts
|

Looking back to the future: a message for a new generation of medical educators

Abstract: The following lessons have been learned. (i) People are important as role models and collaborators. (ii) Innovation in medical education is a complex process and research findings can easily be misinterpreted. (iii) Nudges, interventions that encourage rather than mandate change, are valuable. (iv) Students are important players in planning, delivering and evaluating a curriculum. Each student has different needs and aspirations. They are the 'digital natives'. (v) Offer stakeholders practical solutions to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Taking into account that innovation in medical education is not an easy task [1], a considerable body of knowledge about cognitive processes and methods of teaching and learning has accumulated in recent decades, helping teachers to determine the most efficient way to teach. Scientific evidence has shown that active student participation facilitates the assimilation and consolidation of new knowledge, and improves learning outcomes [25].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account that innovation in medical education is not an easy task [1], a considerable body of knowledge about cognitive processes and methods of teaching and learning has accumulated in recent decades, helping teachers to determine the most efficient way to teach. Scientific evidence has shown that active student participation facilitates the assimilation and consolidation of new knowledge, and improves learning outcomes [25].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes investigated here may not be optimal, and the applicability of these conclusions to different institutional settings may not be appropriate; however, the main proposal that an integrated spiral curriculum is deemed appropriate by the end‐users of the exposure, that is the students, has been substantiated by this study. To capture further student insights and involve these in curriculum planning, as recommended by Harden , it is suggested that further appraisal of the spiral curriculum is undertaken with student focus groups, to gain clarity and perspicacity from the student perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Harden notes that it is important ‘ not to underestimate students’ potential input to the curriculum. They are important stakeholders; they can make important contributions to curriculum planning and they can be drivers for change’ . Ali et al.…”
Section: Introductionmentioning
confidence: 99%
“…The sentiment expressed by John of Salisbury (and later popularised by Newton) has become a tad clichéd, I know, but sometimes ideas become clichéd because the words that describe them are just too perfect. They fit so well in health professional education research that one‐third of this issue of Medical Education has been allotted to three individuals who personify Bernard of Chartres’ giants: Ronald Harden, 2 Geoffrey Norman 3 and Henk Schmidt 4 . We put this issue together in part to celebrate their many accomplishments, in part to thank them for providing the shoulders onto which many of us try to climb, and in part because, while Harden, Norman and Schmidt personify giants as individuals, their collective also provides a worthy metaphor representative of the field of health professional education itself.…”
mentioning
confidence: 97%